Resting Tendon Cross-Sectional Area Underestimates Biceps Brachii Tendon Stress: Importance of Measuring During a Contraction - Smart, Rowan R.; O'Connor, Brian; Jakobi, Jennifer M. (Frontiers in Physiology, 2021)
Force produced by the muscle during contraction is applied to the tendon and distributed through the tendon’s cross-sectional area (CSA). This ratio of force to tendon CSA is quantified as the tendon mechanical property of stress. Stress is traditionally calculated using resting tendon CSA; however, this does not take into account reductions in CSA resulting from tendon elongation during contraction. It is unknown if calculating tendon stress using instantaneous CSA during contraction significantly increases values of in vivo distal biceps brachii tendon stress in humans compared to stress calculated with resting CSA. Nine young (22±1 yrs) and nine old (76±4 yrs) males, and eight young-females (21±1 yrs) performed submaximal isometric elbow flexion tracking tasks at force levels ranging from 2.5% to 80% maximal voluntary contraction (MVC). Distal biceps brachii tendon CSA was recorded on ultrasound at rest and during the submaximal tracking tasks (instantaneous). Tendon stress was calculated as the ratio of tendon force during contraction to CSA using resting and instantaneous measures of CSA, and statistically evaluated with multi-level modelling and Johnson-Neyman regions of significance tests to determine the specific force levels above which differences between calculation methods and groups became statistically significant. Tendon CSA was greatest at rest and decreased as force level increased (p<0.001), and was largest in young-males (23.0 ± 2.90 mm2) followed by old-males (20.87 ± 2.0 mm2) and young-females (17.08 ± 1.54 mm2) (p<.001) at rest and across submaximal force levels. Tendon stress was greater in the instantaneous compared to resting CSA condition, and young-males had the greatest difference in tendon stress values between the two conditions (20±4%), followed by old-males (19±5%) and young-females (17±5%). The specific force at which the difference between instantaneous and resting CSA stress values became statistically significant was 2.6% MVC, 6.6% MVC and 10% MVC for old-males, young-females and young-males, respectively. The influence of using instantaneous compared to resting CSA for tendon stress is both sex-specific in young adults, and age-specific in the context of males. Instantaneous CSA should be used to provide a more accurate measure of in vivo tendon stress in humans.